Developing Convict Criminology Beyond North America. (June 2014) - Ross, Jeffrey Ian; Darke, Sacha; Aresti, Andreas; Newbold, Greg; Earle, Rod
Despite its original vision of a community of ex-convict criminological and criminal justice experts, Convict Criminology (CC) has had difficulty with international expansion and has remained largely a North American movement. There are many reasons why this has occurred. This article reviews the efforts that have been made to internationalize CC in Europe and discusses some of the barriers it has faced. It also suggests prospects for moving the field forward in a truly international manner and the challenges that this entails.